Influence of workpiece thickness and cutting speed to kerf shape and stria formation in laser cutting of acrylic resin plate - K. Saifullah; Mohd Sofian, Mohammad Rosbi; Md Tasyrif, Abdul Rahman; A.S., Fathinul-Syahir; I. Ishak (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.